Providensi Allah Terhadap Umat Pilihan - Deni Nurniat Gulo; Oren Siregar (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
Maintenance, namely God’s continuous action to strive for the preservation of the existence of His creation. Maintenance is very important for the attitude of Christian life, meaning that people who bealive in God are able to live in certainty where God is present and active in the lives of believers. Where when God’s maintenance occurs, there is no doubt, indecision in living life because believers live in God’s definite maintenance. Maintenance is also an action that occurs continuously from divine power in which the creator protects all of His creatures.